Strategi Marketing Mix Dalam Meningkatkan Jumlah Kunjungan Pasien Di Klinik “M” Kota Tasikmalaya - Sugiaman, Helga Audelia; A. Rohendi; Rinawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
Clinic M in Tasikmalaya City has experienced a reduction in patient numbers during the past four years. This study aims to assess the strategy, implementation, and obstacles of the marketing mix in increasing patient visits at Clinic M in Tasikmalaya City. The research findings are expected to aid the Head of the Clinic and staff in developing a marketing strategy designed to increase public interest in visiting Clinic M in Tasikmalaya City, consequently positively influencing patient volume and clinic revenue. The utilized research methodology is descriptive qualitative analysis. The applied data collection strategy included interviews, along with observational and literary techniques. Analytical techniques utilizing SWOT analysis. The study's findings reveal that Clinic M in Tasikmalaya City, based on the SWOT analysis model, is situated in Quadrant I, indicating an aggressive strategy. Diverse methods can be employed by leveraging strengths to exploit opportunities. Alternative strategies for Clinic M in Tasikmalaya City, based on the SWOT analysis, encompass the proficient execution of systems and procedures, augmentation of educational and training initiatives for personnel, expansion of marketing efforts and market share, and strengthening of partnerships with other organizations.